Comparison of the Effectiveness of Mode-Based Schema Therapy and Rumination-Focused Cognitive Behavioral Therapy on Psychological Capital in Women Seeking Cosmetic Surgery with Histrionic Personality Disorder Symptoms - Yazdani, Saeideh; Moraveji, Mahtab; Seirafi, Mohammad Reza; Zarghami, Elham (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to compare the effectiveness of mode-based schema therapy and rumination-focused cognitive behavioral therapy (RFCBT) on psychological capital in women seeking cosmetic surgery with symptoms of histrionic personality disorder. This study employed a quasi-experimental design with pre-test, post-test, and follow-up phases across three parallel groups. The statistical population consisted of women referred to cosmetic surgery clinics in Isfahan during 2024–2025, from whom 75 participants were selected using convenience sampling after screening for histrionic personality disorder symptoms via the MCMI. Participants were randomly assigned into three groups: schema therapy (n = 25), RFCBT (n = 25), and control (n = 25). Both intervention groups received 12 weekly 90-minute group sessions based on standardized protocols, while the control group remained on a waiting list. Data were collected using the Psychological Capital Questionnaire (PCQ) and analyzed using repeated measures ANOVA and Bonferroni post-hoc tests in SPSS-26. The results of repeated measures ANOVA revealed a significant main effect of time (p < 0.01) and a significant main effect of group (p < 0.01) on psychological capital, indicating overall changes across measurement phases and differences between groups. Moreover, the interaction effect of time × group was statistically significant (p < 0.01), demonstrating that the pattern of change differed across the three groups. Bonferroni post-hoc comparisons showed no significant difference between the schema therapy and RFCBT groups at post-test (p > 0.05) and follow-up (p > 0.05), although both interventions produced significantly greater improvements compared to the control group (p < 0.01). Both mode-based schema therapy and rumination-focused cognitive behavioral therapy are effective interventions for enhancing psychological capital in women seeking cosmetic surgery with histrionic personality disorder symptoms, with no significant difference in their effectiveness, suggesting that each approach can be appropriately utilized depending on clinical needs and treatment context.